Modification of the microbiota in obese individuals following a Very Low-Calorie Ketogenic Diet - Casillo, Maria; Monda, Vincenzo; Polito, Rita; Limone, Pierpaolo; Dipace, Anna; Villano, Ines; Messina, Giovanni; Chieffi, Sergio; Messina, Antonietta; Allocca, Salvatore; Ricci, Mariateresa; Moscatelli, Fiorenzo; et al. (Progress in Nutrition, 2024)
Background and aim: Recent studies have shed light on the efficacy of Very Low Carbohydrate Ketogenic Diets (VLCKDs) in combating obesity. This review aims to explore the mechanisms by which VLCKDs influence weight loss, particularly through their interaction with the gut microbiota and modulation of the Enteric Nervous System (ENS). The symbiotic relationship between the gut microbiota and its host is essential for maintaining physiological homeostasis, and disturbances in this relationship can lead to various health issues, including obesity.Methods: This review synthesizes findings from various studies that examine the impact of VLCKDs on the gut microbiota and ENS, and their subsequent effects on obesity. It delves into the dynamics of gut microbiota-host interactions and how VLCKDs can lead to a beneficial remodeling of the gut microbial ecosystem.Results: Evidence suggests that VLCKDs can significantly alter the composition of the gut microbiota, leading to a state that favors weight loss and metabolic health. The diet's ability to modify the gut microbiota and ENS interaction plays a critical role in its effectiveness in reducing obesity and potentially rectifying gut dysbiosis.Conclusions: VLCKDs have been confirmed to be effective in reducing obesity through their significant therapeutic potential, which includes modulating the gut microbiota and the ENS. The restoration of a balanced gut microbiota is crucial for combating obesity and its associated pathologies. VLCKDs emerge as a promising therapeutic approach, suggesting a paradigm shift in the treatment of obesity and related conditions by leveraging dietary interventions to manipulate the gut ecosystem.